(untitled) - Paul Carne (Cambridge, UK, 2000)
This collection of four complte practice tests for the revised Cambridge First Certificate in English examination. The practice tests follow precisely the specifications of the 1996 syllabus
Keywords: english language - examinations - study guides,english language - study and teaching,english language - textbooks for foreign speakers,test of english as a foreign language - study guides